2014
DOI: 10.1111/asj.12255
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic mild food restriction on behavior and the hypothalamic malonyl‐CoA signaling pathway

Abstract: Depression induces anorexia, leading to suppressed feeding behaviors and energy intake. Previously, we revealed that chronic social defeat induced a mild suppression of feeding in rats with elevated levels of hypothalamic malonyl-CoA which regulates feeding. Therefore, we attempted to elucidate the effects of chronic mild food restriction on behavior and on hypothalamic malonyl-CoA. The chronic mild food restricted rats were fed a restricted diet approximately 80% to 90% amount of diet compared to the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…Similarly, increased hypothalamic energy and mitochondrial metabolism may be the consequence of food anticipatory activity. In the same way, we observed that AMPK was less activated in the hypothalamus of LFA and ABA mice while other studies previously showed activation of AMPK after food deprivation 50 , 51 . However, hypothalamic AMPK can be affected by stress, i.e.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, increased hypothalamic energy and mitochondrial metabolism may be the consequence of food anticipatory activity. In the same way, we observed that AMPK was less activated in the hypothalamus of LFA and ABA mice while other studies previously showed activation of AMPK after food deprivation 50 , 51 . However, hypothalamic AMPK can be affected by stress, i.e.…”
Section: Discussionsupporting
confidence: 84%
“…Some of the largest consumers of NADPH include the enzymes for the biosynthesis of fatty acids, cholesterol, steroids, and deoxyribonucleotides [48]. During CR, AMP kinase (AMPK) becomes activated [254], prominently in the hypothalamus [255]. AMPK phosphorylates acetyl-CoA carboxylase to inhibit fatty acid synthesis [255].…”
Section: Calorie Restriction May Extend Lifespan In Part Through mentioning
confidence: 99%
“…During CR, AMP kinase (AMPK) becomes activated [254], prominently in the hypothalamus [255]. AMPK phosphorylates acetyl-CoA carboxylase to inhibit fatty acid synthesis [255]. This inhibition of fatty acid synthesis leads to the activation of fatty acid beta-oxidation (except in neurons that lack these enzymes) to provide cellular energy and prevent a futile cycle of fatty acid synthesis and breakdown.…”
Section: Calorie Restriction May Extend Lifespan In Part Through mentioning
confidence: 99%
“…Interestingly, reducing the number of calories consumed promotes the survival of newly generated cells in the hippocampus [36,37]. Furthermore, chronic mild food restriction activates AMPK following decreased hypothalamic malonyl-CoA, an inhibitor of fatty acid oxidation [38].…”
Section: Antidepressant Effects Of Caloric/ Dietary Restrictionmentioning
confidence: 99%